Hope and Fulfillment After Complex Trauma: Using Mixed Methods to Understand Healing - Saint Arnault, Denise; Sinko, Laura (Frontiers in Psychology, 2019)
Research has shown that the experience of Childhood Sexual Abuse (CSA) can increase the rates of physical and emotional sequela, including depression, anxiety, PTSD, and physical pain. However, little is known about the healing journeys for those women who, after surviving CSA, also experience unwanted sexual assaults (USE) as a young adult. The goal of this mixed method study is to compare identity, distress, and positive health outcomes for survivors of CSA and USE with those of women who have survived USE alone. First, 206 women completed a survey that evaluated mental health distress, trauma centrality, and health indicators, and these women were invited to take part in an additional interview. A subsample of 24 women agreed to be interviewed with a narrative interview that examined trauma recovery from a holistic perspective. Thematic analysis of the interview data revealed contextual and internal barriers and facilitators of healing. Eight qualitative dimensions were derived from code frequencies of the emerging 50 qualitative codes, including Normalization, Denial, Negative Impact, Positive Coping, Rumination, Identity Healing, Hope and Fulfillment Healing, and Engagement Healing. We then used t-tests to compare the mean code frequencies of these code complexes for survivors of CSA/USE and USE alone, and the significant findings revealed hypotheses to be tested in the larger quantitative sample. H1: Survivors of CSA have less denial than USE alone; H2: Survivors of CSA have higher Negative Impact scores than USE alone, and H3: Survivors of CSA have more Hope and Fulfillment than USE alone. H1 was supported; survivors of both CSA and USE had a significantly higher mean Centrality Scores than Survivors of USE alone. H2 was supported, and all negative impact scores were significantly higher for the survivors of both CSA and USE than survivors of USE alone. H3 was partially supported. Survivors of both CSA and USE had significantly higher mean Post-Traumatic growth scores. However, survivors of USE alone had significantly higher means for Sense of Coherence and Self-Compassion scores. Implications for practice are discussed.